Perbandingan Profitabilitas Industri Perbankan Syariah dan Industri Perbankan Konvensional Menggunakan Metode Struktur Kinerja dan Perilaku - Amalia, Fitri; Nasution, Mustafa Edwin (UI Scholars Hub, 2007)
Positive correlation between concentration and profitability is not always a result of collusion. Market concentration can be a proxy for efficiency and product differentiation that have done by company. The company that can be mentioned efficient and have done product differentiation can improve market share, and industry that consist of the company has tendency to be concentrated. This research tries to prove whether market share and concentration in Islamic and conventional banking industry as proxy to efficient. If it is proven, so there is no relationship between market share and concentration with profitability. It is appropriate with efficient structure hypothesis. Using pool data for Islamic and conventional banking industry at period January 2002 until November 2005. Model that had been used in this research is adjusted Smirlock model with fixed effect method from this research, is hoped that Islamic banking industry can support efficient structure hypothesis, moreover conventional banking industry can support differentiation hypothesis.